Extended Reality for Teleoperated Mobile Robots - Batistute, Arturo; Santos, Edvaldo; Takieddine, Karam; Lazari, Pedro Machado; Rocha, Lidia Giane Da; Vivaldini, Kelen Cristiane Teixeira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
Human-Robot Interaction (HRI) will be a crucial component of intelligent factories of the future (FoF). Nevertheless, several research indicates that robot teleoperation can be challenging and, therefore, impose high requirements on user training and expertise. The emerging technology of Extended Reality, the umbrella for immersive technologies associated with different types of realities, has recently been applied to create novel developer tools in industrial robotics, with the potential to increase user-friendliness and minimize requirements on user training and operator’s previous expertise. This paper evaluates the robot teleoperation efficiency achieved by a number of users performing a given task, using the traditional keyboard method and two forms of extended realities. Results showed the advantages of teleoperation based on extended realities, with respect to user friendliness, less operational errors, and efficiency and effectiveness.